Strength of lashings used in bamboo connections under simulated typhoon loads - Chavez, Romualdo A. (1989)
Split Cane or Rattan and nylon lashings used in bamboo cross connections were tested to characterize their static and fatigue behavior. Single line and full-scale lashed configurations were loaded in static and cyclic tensile modes simulating typhoon-induced forces. Both configurations and materials exhibited fatigue damage under cyclic load. Single line specimens' behavior was fitted to Brown's cumulative damage model giving parameter r of 1.9 , 13.3, and 9.5 for rattan and two types of nylon respectively. Full--scale specimens exhibited similar behavior. Therefore, prediction of damage or fatigue life using the model is reasonable. Static capacity of lashed connections can be estimated from single line strengths using a lashing factor of 0.73, 0.83, and 0.78 for rattan and two types of nylon respectively. Strength properties of single line specimens were derived. Replication of full-scale fatigue tests was recommended for application to engineering design.
Thesis (M.S.)--University of the Philippines, Diliman.
Typescript.
Keywords: Bamboo construction -- Philippines; Building materials; Dwellings -- Natural disaster effects